Case report: A case of blood culture-negative Bartonella quintana endocarditis: blood mNGS is an efficient method for early diagnosis - Pu, Jun-fan; Zhou, Yan-ling; Deng, Min; Wu, Jing (Frontiers in Medicine, 2024)
Bartonella quintana is one of the main causes of blood culture-negative endocarditis, and routine blood culture and serological methods are difficult to achieve early diagnosis. We report a case of blood culture-negative Bartonella quintana endocarditis from southwestern Chongqing. The patient was a 67-year-old male scavenger who presented with heart failure without fever as the main clinical manifestation upon admission. He stated having had contact with stray cats in the past two months. The combination of clinical symptoms, echocardiography, and blood mNGS testing confirmed the infection of Bartonella quintana.A 67-year-old male scavenger from a rural area in western Chongqing presented to the Dazu District People's Hospital three weeks ago due to worsening edema, chest tightness, shortness of breath, and chest compression during daily activities. The patient had a history of bilateral lower extremity edema for ten years without obvious inducing factors. The edema was symmetrical and pitting, which usually improved after rest. The patient denied any history of chronic diseases such as